IMPLEMENTASI PENDEKATAN JOYFUL LEARNING MENGGUNAKAN MEDIA ALAM AQUASCAPE DALAM MENINGKATKAN KREATIVITAS ANAK DI DAYCARE CAHAYA PERMATA PASAR KEMIS - Dewi Setianti; Nikem Kurnia Ningsih (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
This study aims to describe the implementation of the joyful learning approach using aquascape natural media in daycare to increase children's engagement and learning experience. The research subjects consisted of 11 children and 2 teachers at a daycare. This study used a qualitative approach with descriptive methods. Data collection techniques were carried out through observation, interviews, and documentation during the learning activities. The results showed that the use of aquascape natural media in the joyful learning approach was able to create a fun, interactive, and meaningful learning atmosphere. Children showed an increase in curiosity, observation skills, courage to ask questions, and a caring attitude towards the environment. The role of the teacher as a facilitator is very important in directing children's exploration of simple ecosystems in aquascapes. In addition, this activity also supports the development of children's cognitive, social-emotional, language, and fine motor aspects. Thus, the implementation of the joyful learning approach through aquascape natural media is effective in creating an active and enjoyable learning experience in a daycare environment. Concrete and contextual natural media can be an innovative alternative in early childhood learning.